The Symbolic Meanings of the Lengger Mask Dance in the Sedekah Bumi Ceremony of Kaliputih Village - Nugro Widiyanto; RM. Teguh Supriyanto (Sutasoma : Jurnal Sastra Jawa, 2026)
The Lengger Mask Dance during the Sedekah Bumi Ceremony in Kaliputih village is a sacred tradition rich in symbolic meaning and is still maintained amid modernization. This research aims to uncover the symbolic meanings in the songs, movements, makeup, and dance clothes of the Lengger Mask, and to explain how the community maintains its sustainability as a means of preserving local wisdom. This research uses a qualitative method with an ethnographic approach combined with an ethnopedagogical perspective, through participatory observation, in-depth interviews, and documentation of traditional actors, traditional leaders, village officials, and communities. The data is analyzed using an interactive model through reduction, presentation, and conclusion drawing. The results of the study show that the symbols in the Lengger Mask Dance represent the cosmological relationship between humans, ancestors, nature, and God through the structure of the song, the variety of movements, and the performance's attributes. In addition, tradition is preserved through intergenerational inheritance, communal commitment, and the revitalization of cultural values in the practice of the Sedekah Bumi ritual. This study concludes that the symbolic meaning of the Lengger Mask Dance is the primary foundation for the sustainability of tradition and for strengthening cultural education in the community.